An ethnogeography of the maleku indigenous peoples in northern Costa Rica - Castillo Vásquez, Roberto 1962 - (2004)
Tesis (doctor of philosophy)--Department of Geography and the Faculty of the Graduate School of the University of Kansas, 2004.